The Emergence of the Placial-Technical: Digital Placemaking as Information Practice - Suzuki, Takayuki; Dillon, Andrew (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie, 2025)
In an era of ubiquitous computing and generative AI, our experience of place is increasingly mediated by digital technologies, creating hybrid environments where physical and virtual interactions converge. While fields like media and urban studies have explored this through the concept of ‘digital placemaking’—the use of digital media to create a sense of place—this phenomenon has received limited attention within information studies. This paper addresses this gap by proposing a new conceptual framework, termed the ‘placial-technical,’ which refines the traditional socio-technical perspective to specifically analyze the mutual shaping of place, information, and technology. Using this lens, we argue that digital placemaking should be understood as a form of information practice, encompassing the socially situated ways individuals seek, use, and share information to construct meaning about their surroundings.Drawing on literature from human geography, media studies, and Human Computer Interaction, we trace the evolution of placemaking concepts and technologies. We then analyze digital placemaking through the dual processes of perception (how information inputs shape our understanding of place) and representation (how we create informational outputs to depict place), focusing on the growing influence of algorithms and generative AI. This synthesis reveals research gaps and offers implications for information studies. By conceptualizing digital placemaking as an information practice, the field can extend its theoretical and methodological tools while informing the ethical design of technologies that foster authentic community engagement and place attachment in a digitally mediated world.